Grain Boundaries in Methylammonium Lead Halide Perovskites Facilitate Water Diffusion - Fuyu Tian (Wiley-VCH, 2021)
Organic–inorganic hybrid perovskites such as methylammonium lead iodide (MAPbI3) materials have recently attracted great attention due to their potential for photovoltaic applications. The performance and stability of these perovskite solar cells are sensitive to water and moisture in an ambient environment. Thus, an understanding of how water influences MAPbI3 and particularly the role of grain boundary (GB) defects is important for developing appropriate mitigation strategies. Herein, water molecular diffusion in ∑5‐(210) GB is investigated and compared with pristine MAPbI3 using first‐principles calculations. Water diffusion along the ∑5‐(210) GB is found to be facile with a 0.07 eV energy barrier while diffusion barrier from GB core to bulk is 0.24 eV. In contrast, the diffusion process in bulk MAPbI3 is relatively large 0.70 eV due to water interactions with the Pb–I network. Further, it is shown that water is more stable in the GB region compared with the pristine system. Thus, the strong thermodynamic and kinetic tendencies for water segregation to the GBs in MAPbI3 suggests that improving the crystallinity of MAPbI3 is an effective strategy to slow down water degradation processes in agreement with recent experimental results.